Uncertainty analysis of data collected using embedded magnetic particle velocity gauges - Finnegan, Simon; Appleby-Thomas, Gareth J.; Hazael, Rachael; Ferguson, J. W.; Goff, Michael J. (American Institute of Physics (AIP), 2023)
The uncertainties in particle velocity and position-time data collected using embedded magnetic gauges are presented. Data were also collected on the resistance change of gauge elements under shock loading and the effect of the element width, as opposed to length, on the observed rise times, as two factors that can affect the data quality and uncertainty analysis. A new method of fitting to the shock tracker data is also proposed. The data were collected using gas gun experiments on Comp-B and PCTFE targets. For a well characterized setup, the uncertainty in the particle velocity data can be reduced to such a level that noise and other ‘random’ variations in the data can be more significant. This highlights the importance of reducing these factors and collecting high quality data but also investigating additional sources of error, such as the resistance change of the elements under shock loading, in order to determine the true uncertainty.